Perkawinan Bawah Umur dan Potensi Perceraian (Studi Kewenangan KUA Wilayah Kota Bogor) - Ani Yumarni; Endeh Suhartini (Jurnal Hukum IUS QUIA IUSTUM, 2019)
This study examines: first the authority of VAT on Religion Affair Office (KUA) in Sub district of Bogor City Region in creating an orderly administration of registering the underage marriages, and secondly the assessment of the relevance of underage marriage with the high divorce rates in Bogor City Region.This is an empirical juridical research. From the results of this research, it can be concluded that, first, the  VAT  Institution  in  Bogor  City  has  made  some  maximum  efforts  to  create  the  orderly  marital administration as mandated by law. It is also reaffirmed by the Circular of the Ministry of Religion of RI regarding  the  implementation  of  the  Marriage  Administration  System  (SIMKAH),  which  increasingly narrows  the  space  for  people  to  do  an  underage  marriage.  Second,  the  prevalence  of  underage marriage has the relevance to the high divorce rate also dominated by couples aged 21-30 years. It is because even if the marriage is 'not registered', due to being underage according to the law, it still has an  opportunity  to  obtain  legality  through  legal  action  to  submit  a  marriage  permit  application  in  the Religious  Court.  In  addition,  emotional  immaturity and  household  unpreparedness  are  the  factors  of high divorce among young couples undergoing an underage marriage.